Genetic evaluation of the Baja California rock squirrel Otospermophilus atricapillus (Rodentia: Sciuridae) - Álvarez-Castañeda, Sergio Ticul; Cortés-Calva, Patricia (Zootaxa, 2011)
The Baja California rock squirrel (Otospermophilus atricapillus Bryant) is endemic to the Baja California Peninsula, Mexico and known from only five localities. O. atricapillus is considered as the sister species of O. beecheyi (Richardson) and both have been considered different species mainly by its colorations. In an attempt to better understand the relationship within O. atricapillus and with its sister species O. beecheyi, we used genetic information gathered from O. atricapillus, aiming to investigate the phylogenetic and phylogeography of O. atricapillus O. beecheyi. We analyzed two sets of mitochondrial cytochrome b gene (Cyt b) data: One 800 (bp) fragments of 118 individuals and a second one of 1140 (bp) for the 32 haplotypes found. Our own hypothesis is that specific characteristics used to distinguish O. artricapillus from O. beecheyi are at the same level than the differences among the recognized subspecies of O beecheyi. Under that condition, a genetic analysis will show that O. atricapillus are within the genetic variation of O. beecheyi, and the current diagnostic characters of O. atricapillus could be considered only at subspecific level. The analysis of molecular variance revealed that O. atricapillus is not significantly different from O. beecheyi, and that, apart from highland populations in the Sierra Nevada, the sampled populations of O. beecheyi and O. atricapillus are not significantly different among all of them.